Waiting to Inhale: Reducing Stigma in the Medical Cannabis Industry. (June 2020) - Lashley, Kisha; Pollock, Timothy G.
When a new industry category is predicated on a product or activity subject to "core" stigma—meaning its very nature is stigmatized—the actors trying to establish it may struggle to gain the resources they need to survive and grow. To explain the process of reducing an industry category's stigma, we take an inductive approach to understanding how actors in the U.S. medical cannabis industry collectively attempted to create and disseminate a moral public image based on healing and patients' rights. We find that reducing category-level core stigma is a phased effort that takes place across different relational spaces. A moral agenda based on broadly acceptable values jumpstarts the process, and the industry then creates a new moral prototype reflecting these values that industry actors can identify with. Category members must publicly disidentify with the current, stigmatized prototypes and infuse the new moral prototype among their stakeholder audiences through their language and practices, creating emotional connections that lead to cognitive acceptance. This process is messy, as individual organizations often need to continue engaging in stigmatized behaviors to survive, even as they publicly disidentify with them. Our process model also identifies ways in which category emergence in core-stigmatized categories differs from the process for non-stigmatized categories.